Genetic diversity and population structure of Epichloë fungal pathogens of plants in natural ecosystems - Treindl, Artemis D.; Stapley, Jessica; Leuchtmann, Adrian (Frontiers in Ecology and Evolution, 2023)
Understanding the population genetic processes driving the evolution of plant pathogens is of central interest to plant pathologists and evolutionary biologists alike. However, most studies focus on host-pathogen associations in agricultural systems of high genetic and environmental homogeneity and less is known about the genetic structure of pathogen populations infecting wild plants in natural ecosystems. We performed parallel population sampling of two pathogenic Epichloe species occurring sympatrically on different host grasses in natural and seminatural grasslands in Europe: E. typhina infecting Dactylis glomerata and E. clarkii infecting Holcus lanatus. We sequenced 422 haploid isolates and generated genome-wide SNP datasets to investigate genetic diversity and population structure. In both species geographically separated populations formed genetically distinct groups, however population separation was less distinct in E. typhina compared to E. clarkii. The patterns of among population admixture also differed between species across the same geographic range: we found higher levels of population genetic differentiation and a stronger effect of isolation by distance in E. clarkii compared to E. typhina, consistent with lower levels of gene flow in the former. This pattern may be explained by the different dispersal abilities of the two pathogens and is expected to be influenced by the genetic structure of host populations. In addition, genetic diversity was higher in E. typhina populations compared to E. clarkii, indicative of higher effective population size in E. typhina. These results suggest that the effect of genetic drift and the efficacy of selection may differ in the two species. Our study provides evidence of how ecologically similar species occupying the same geographical space can experience different evolutionary contexts, which could influence local adaptation and coevolutionary dynamics of these fungal pathogens.